Data monetisation : a story of dashmote - Yang, Shengyun (London : Rotterdam School of Management, Erasmus University, 2024)
Founded in 2014, Dashmote was a rapidly growing and globally operating Software as a Service (SaaS) company based on its Artificial Intelligence (AI), natural language processing and visual recognition technologies. The founders aimed to guide people toward success in an AI and data-driven world by improving their understanding of the world of visual content and unlocking the value behind the massive amount of online and offline data. By the end of 2018, they had decided to focus on the use of their solution ‘Location Intelligence’ in the beverage and fast-moving consumer goods (FMCG) industries. Their service turned data into actionable business insights for their clients. In 2019, the company grew from 20 to 65 employees. Scrum was adaptively implemented in its project management. In 2020, the company expanded its global footprint to 17 new countries and increased its annual recurring revenue by 193%. The ongoing transformation was noticeable and evident in every aspect of Dashmote’s business. The company continued to establish itself as a leading global SaaS business. The fundamental and constant question to the founders and management team was how they could further expand in a scalable way and help people and organisations through technology.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business -- Technological innovations -- Case studies; Management information systems -- Case studies; Decision-making -- Case studies